MODELS OF GOVERNMENTAL CRISIS COMMUNICATIONS AND INFORMATION MANAGEMENT - E. A. Gryzunova (Vestnik MGIMO-Universiteta)
The research deals with the information system of public administration aimed at decision-making and communication with the society in a crisis. The system’s functionality depends on adequacy of goal-setting and on correspondence of the chosen strategy to a crisis type which differ by social response. The author substantiates traditional model of crisis communications and information management for solving conflict crises, while consensus crises require participative model, and polemic crises are recommended to be managed by negotiation and dialogue facilitation model. The negotiation and dialogue facilitation model for managing polemic crises is aimed at realization of a communicative action concept advocated by J. Habermas. As long as modern complex crises require participation of multiple actors which have different visions of a crisis situation and specific interests, “crisis decision making in such context can be seen as a negotiation process” [16]. On the level of information processing the primary step is to discover both major crisis tendencies in each of the core social systems, and social groups whose opinions and interests should be considered. After that definition of possible crisis triggers, forecasting and crisis planning are realized taking into consideration interests and expert recommendations of different social groups’ representatives. Two basic ways of coordination are suggested: public discussion of issues, or collaborative problem-solving. The first way requires organization of a public dialogue in a form of discussion, citizen jury, or negotiations. Coordination through collaborative problem-solving implies fragmentation of a complex subject which means reducing it into concrete practical questions that require discussion and decision-making. Communication within the framework of the described model is remarkable for the supra-communicative practice of facilitating the interaction of the crisis management participants.